Assessment of knowledge and practices regarding menstrual hygiene among adolescent girls of Government higher secondary school, station Murhipar, Rajnandgaon (C.G.) - Tiwari, Anjana; Ekka, Indu Jyotsna; Thakur, Rajni (International Journal Of Community Medicine And Public Health, 2018)
Background: Poor menstrual hygiene practices result into adverse health outcome in terms of increased vulnerability to reproductive tract infections (RTIs) and its consequences. The objective of present study was to assess the Knowledge and Practices regarding menstrual hygiene among adolescent school girls. Methods: A community-based, cross-sectional study was done among adolescent girls of class VII, VIII, IX and X (who attained menarche) in Government higher secondary school, station Murhipar, Rajnandgaon (C.G.) during September 2017 to October 2017 (two months) using a pre-designed, pre-tested questionnaire. Statistical analysis: Collected data was analyzed by using descriptive statistics (frequency and percentage). Results: A total of 141 adolescent school girls in the age group 12 to 17 years participated in this study. The mean age of menarche of the respondents was 12.9 years (range 11-15 years). Majority of girls (85.8%) were aware about menstruation prior to attainment of menarche. Mother was the first informant in case of 55.4% girls. Majority of girls (90.1%) practiced different restrictions during menstruation. Only 2.1% girls used sanitary pads during menstruation. Regarding hygienic practices, only 29.8% of girls change their cloths/pads three and above times per day and 98.6% girls had daily bath with soap during menstruation. Satisfactory hand washing with soap and water after changing pad during menstruation was present in 96.4%. Cleanliness of external genitalia was satisfactory in case of 80.1% girls. Conclusions: The adolescent girls need to be educated about fact of menstruation and menstrual hygiene practices in order to improve the menstrual hygiene.